360° Virtual learning experience on good agricultural practices for potato production - Sharma, K.; Atieno, E.; Vandamme, Elke; Nkomo, Mandlenkosi (International Potato Center, 2023)
Virtual learning tour provides unique 360° virtual experience on the entire potato cultivation process, from soil preparation to harvest and post-harvest handling, each section provides valuable insights into the art and science of successful potato farming.